2011
DOI: 10.1177/138826271101300301
|View full text |Cite
|
Sign up to set email alerts
|

Activating the Unemployed — Directions and Divisions in Europe

Abstract: One of the continuously disputed issues of research on welfare state reform is the question of convergence or divergence. Despite much reform in the direction of an activating kind of unemployment policy, for example, differences between these unemployment policies remain. These differences are often attributed to different types of welfare regimes. This article departs from the assumption that policy changes have brought about changes in diversity. It proposes a two-dimensional model of activation, putting fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 31 publications
0
28
0
1
Order By: Relevance
“…Marchal and Van Mechelen (2013), in line with other observers (e.g., Dean, 2003), suggested that, like those of other Nordic countries, Norwegian activation frontline work is characterised by a relatively strong emphasis on the enabling dimension in terms of various skill-enhancing activities (Hagelund, 2016), with inclusion in the labour market as the primary focus. Although activation work is mainly a mix of demanding and enabling elements (Aurich, 2011), the emphasis that is put on the enabling elements in the Norwegian context will plausibly have implications for service provision and frontline workers' attitudes and everyday practices. The enabling orientation being less harsh and less controversial than more demanding orientations might to some extent limit the extent of negative frontline worker attitudes towards the policy.…”
Section: Activation and Conditionality As Frontline Workmentioning
confidence: 99%
“…Marchal and Van Mechelen (2013), in line with other observers (e.g., Dean, 2003), suggested that, like those of other Nordic countries, Norwegian activation frontline work is characterised by a relatively strong emphasis on the enabling dimension in terms of various skill-enhancing activities (Hagelund, 2016), with inclusion in the labour market as the primary focus. Although activation work is mainly a mix of demanding and enabling elements (Aurich, 2011), the emphasis that is put on the enabling elements in the Norwegian context will plausibly have implications for service provision and frontline workers' attitudes and everyday practices. The enabling orientation being less harsh and less controversial than more demanding orientations might to some extent limit the extent of negative frontline worker attitudes towards the policy.…”
Section: Activation and Conditionality As Frontline Workmentioning
confidence: 99%
“…Obvious examples of eligibility criteria are nationality and residence requirements and means tests. However, the shift of social policy measures towards activation has by now been extensively documented (Aurich 2011;Marchal and Van Mechelen 2014b;Immervoll 2012;Kenworthy 2010;Eichhorst and Konle-Seidl 2008). Obligations or behavioural requirements of beneficiaries to ensure continued benefit receipt have been strengthened and made more explicit and should therefore be taken into account when assessing changes in social citizenship.…”
Section: Analytical Framework: Assessing Changesmentioning
confidence: 99%
“…3 An important feature of the Norwegian activation policies has been the emphasis on the so-called 'work-line', expressed by strengthening the qualifying conditions for unemployment, disability and sickness benefits (Drøpping et al, 1991). As opposed to stricter policies (as in the United Kingdom), this approach is based on the generous type of activation policies that emphasise education and training over direct labour market participation; it is often characterised as social investment or enabling activation policies (Gilbert, 2002;Aurich, 2011). The recipients are enabled through activation programmes, using instruments for testing work capability and readiness and stricter follow-up through individual plans.…”
Section: Introductionmentioning
confidence: 99%